Phishing, superstition or healing prayer? chain letters on the Internet - Frauhammer Krisztina (Religion, culture, society, 2018)
In this study I analyse chain letters with a religious content spreading on the internet, by e-mail and on social media. On the basis of content, they can be sorted in separate groups: they transmit prayers, beautiful and instructive stories, wisdoms, and sometimes messages from heaven. In their promises too, they focus mainly on the accumulation of spiritual benefits (they will pray for those who forward the message, they will think of them, they will send them positive energy). In my analysis I examine the genre forerunners of the source group (letters from heaven, sacred letters), and their latest variants that are transmitted in the form of presentation letters. The main question I raise is whether the chain letters are really only well written, persuasive texts that are easy to forward thanks to the technical possibilities of the internet. Or is the forwarding motivated by a belief that the associated positive promises or threats will come true? Or could it be a desire to influence the future, and the rites associated with this? My initial hypothesis is that this is a writing practice with centuries of tradition and the associated beliefs are also ancient. Even if the knowledge they contain sometimes becomes a means for phishing.